Muzykoterapia w pracy z dzieckiem ze spektrum autyzmu = Music therapy in working with an autistic child - Zieja, Elżbieta (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
Music therapy is the oldest and most developed form of therapy through art, and the relationship between music and medicine dates back to the beginnings of human history. For autistic characteristic is disturbed or impossible verbal communication, and there- fore difficult to contact with the environment. Sought methods "reach" to the sick.
Keywords: terapia; dziecko; autyzm; muzykoterapia; therapy; child; autism; music therapy